The alleviating effects and mechanisms of Enterococcus faecium Kimate-X and Lactobacillus plantarum Kimate-F combination on canine inflammatory bowel disease - Zhang, Rui; Hu, Wanjin; Zhong, Saiwei; Chen, Weiyang; Xie, Shuang; Chen, Meiru; Yu, Qinghua (Frontiers in Veterinary Science, 2025)
IntroductionCanine inflammatory bowel disease (IBD) is characterized by chronic intestinal inflammation and dysbiosis. Conventional treatments often result in adverse effects and contribute to antibiotic resistance, highlighting the need for safe, effective alternatives. Probiotics have gained attention for their potential in modulating gut microbiota and immune responses. This study investigates the therapeutic mechanisms of Enterococcus faecium Kimate-X and Lactobacillus plantarum Kimate-F, individually and in combination, in alleviating canine IBD.MethodsIn vitro antibacterial and anti-inflammatory activities were assessed using agar well diffusion assays and LPS-induced RAW 264.7 macrophages, respectively. In vivo efficacy was evaluated in dextran sulfate sodium (DSS)-induced colitis models in mice and dogs. Metagenomic sequencing was performed on canine fecal samples to analyze microbiota composition and functional pathways. Short-chain fatty acid (SCFA) levels were quantified, and key host signaling pathways were examined.ResultsKimate-F showed strong antibacterial effects against Escherichia coli, Salmonella enteritidis, and Yersinia enterocolitica. Kimate-X significantly suppressed nitric oxide (NO) and TNF-α production in the in vitro inflammation model. In both mouse and canine DSS-induced colitis models, the probiotic combination significantly reduced weight loss, colonic damage, and serum inflammatory cytokines, while increasing IL-10 levels. Metagenomic analysis revealed enhanced microbial diversity, with enrichment of Bifidobacterium species and upregulation of metabolic pathways involved in nutrient absorption and immune regulation. The probiotic combination also modulated the PPAR and AMPK signaling pathways and promoted SCFA production in canine feces.DiscussionThese findings suggest that E. faecium Kimate-X and L. plantarum Kimate-F act synergistically to restore gut homeostasis, reduce intestinal inflammation, and enhance host immunity. Their ability to modulate gut microbiota composition, host signaling, and metabolic output underscores their potential as safe and effective probiotic candidates for managing canine IBD.